Discriminate Modelling of Peak and Off-Peak Motorway Capacity - Mohammed Alhassan, Hashim; Parameswaren, Sundara; Johnnie, Ben-Edigbe (International Journal of Integrated Engineering, 2013)
Traffic theory is concerned with the movement of discrete objects in real time over a finite network in 2 Dimensions. It is compatible with or dependent on fundamental diagram of traffic. Without question traffic flow is an essential quantitative parameter that is used in planning, designs and roadway improvements.  Road capacity is significant because it is an important indicator of road performance and can point road managers in the right road maintenance and traffic management direction. In this paper four direct empirical capacity measurement methods have been considered. To test the efficacy of each method, data for peak period, off-peak and transition to peak have been used. The headway and the volume methods lack predictive capability and are suitable only for current assessment of flow rates.  The product limit method is weak in its predictive capability in view of the arbitrariness in the selection of the capacity value. It is also an extreme value method; hence not all volume data can be used with this method. The fundamental diagram method has good predictive capability and furnishes capacity values consistent with the standard of the facility. Unlike other methods, it does not rely on bottleneck conditions to deliver the capacity value.  The paper concluded that each method is uniquely suited to prevailing conditions and can be so employed.